Self‐reported quality of life in long‐term survivors of childhood lymphoblastic malignancy treated with hematopoietic stem cell transplantation versus conventional therapy. Issue 8 (20th March 2013) - Sundberg, Kay K.; Wettergren, Lena; Frisk, Per; Arvidson, Johan
Abstract Background Chronic health conditions are known to be both abundant and severe after pediatric hematopoietic stem cell transplantation (SCT). The present objective was to investigate the impact of disease and treatment on individual QoL and health‐related quality of life (HRQoL) in long‐term survivors of childhood lymphoblastic malignancy treated with conventional therapy versus SCT. Procedure Survivors of lymphoblastic malignancy treated with (n = 18) or without (n = 52) SCT were recruited a median follow‐up time of 18 and 14 years, respectively. The indication for SCT was relapsed disease in 17 of 18 cases. Autologous stem cells were used in 15 cases. Total body irradiation (TBI) was included in the conditioning regimen for all SCT patients. A cross‐sectional study was conducted using two validated instruments: SEIQoL‐DW (individual QoL) and SF‐36 (HRQoL). Content analysis was used to analyze SEIQoL‐DW and an overall QoL index score was calculated. Two multiple linear regression analyses were performed to detect factors influencing outcomes. Results Poorer ratings of overall QoL and more negative consequences related to physical dysfunctions were shown in the SCT group. The findings indicate that being unemployed or on sick leave are associated with a decline in HRQoL and individual QoL rather than SCT, cranial radiation therapy, present age, or sex. Conclusion In this small sample of long‐term survivors of SCT, QoL seems reasonably good and similar to that of those having received conventional therapy. However, managing an employment must be acknowledged as an important part of life that has a great impact on QoL. Pediatr Blood Cancer 2013;601382‐1387. © 2013 Wiley Periodicals, Inc.